Transaction Cost Management Strategies and Practices for a Global Open Economy - Suematsu, Chihiro (Management for Professionals, 2014)
All organizations, institutions, business processes, markets and strategies have one aim in common: the reduction of transaction costs. This aim is pursued relentlessly in practice, and has been perceived to bring about drastic changes, especially in the recent global market and the cyber economy. This book analyzes and describes "transactions" as a model, on the basis of which organizations, institutions and business processes can be appropriately shaped. It tracks transaction costs to enable a scientific approach instead of a widely used "state-of-the-art" approach, working to bridge the gap between theory and practice. This open access book analyzes and describes "transactions" as a model...